Whole-Transcriptome Sequence of Degenerative Meniscus Cells Unveiling Diagnostic Markers and Therapeutic Targets for Osteoarthritis - Jiang, Zongrui; Du, Xue; Wen, Xingzhao; Li, Hongyi; Zeng, Anyu; Sun, Hao; Hu, Shu; He, Qing; Liao, Weiming; Zhang, Zhiqi (Frontiers in Genetics, 2021)
Meniscus plays an important role in joint homestasis. Tear or degeneration of meniscus might facilitate the process of knee osteoarthritis. Hence, to investigate the transcriptome change during meniscus degeneration, we reveal the alterations of message RNA (mRNA), microRNA (miRNA), long noncoding RNA (lncRNA), circular RNA (cirRNA) in meniscus during osteoarthritis by whole transcriptome sequence. A total of 375 mRNAs, 15 miRNAs, 56 lncRNAs, and 90 circRNAs were significantly altered in the degenerative meniscus treated with IL-1β. More importantly, highly specific ceRNA networks regulated by lncRNA LOC107986251-miR-212-5p-SESN3 and hsa_circ_0018069-miR-147b-3p-TJP2 were screened out during interleukin-induced meniscus degeneration, unveiling potential therapeutic targets for meniscus degeneration during the OA process. More importantly, Lipocalin-2 (LCN2), RAB27B were identified as potential biomarkers in menisci degeneration by overlapping three previously constructed databases of OA menisci. LCN2 and RAB27B were both upregulated in Osteoarthritic menisci and IL-1β treated menisci, and were highly associated with the severity of osteoarthritis.This could introduce potential novel molecules into the database of clinical diagnostic biomarkers and possible therapeutic targets for early-stage OA treatment.